Benchmarking Records of Administrators and Officers at Health Deputy Headquarters of Iranian Universities of Medical Sciences: 2008 – 2010 - MR Maleki (مدیریت سلامت, 2011)
Introduction: Benchmarking is used to identify the successful experiences and achievements of a business to develop and improve organizational performance. This study aimed to determine, firstly, the frequency of benchmarking made by administrators and officers at Health Deputy headquarters of Iranian universities of medical sciences and, secondly, the relationship of this frequency to individual and organizational factors.Methods: This cross-sectional study was conducted in spring 2010. The research population constituted administrators and officers at Health Deputy Headquarters of Iranian universities of medical sciences from which thirteen universities were randomized and stratified. All available administrators and officers in the selected universities were interviewed and, then, were asked to complete a reliable and valid questionnaire consisting of individual and organizational variables. Results: From the 293 administrators and officers under study, 75 (26.5%) could exploit 167 cases of successful experiences and achievements of other organizations to improve and develop their organizational performance. While 46.7% of benchmarking was conducted through site visits, 86.2 % of all the process was performed by the health sector, and 91% of the activity was done within the country. Among individual and organizational factors, only the educational degrees of the participants showed a significant relationship with benchmarking rates (ρ=0.045). Discussion: To promote the low amount of benchmarking capita among the administrators and officers, it seems necessary to design and implement intervention programs.